The Influence of Capital Expenditure, Economic Growth, and Fiscal Stress on Local Government Financial Performance - Susanti, Susi; Sam, Iskandar; Yudi, Yudi (Faculty of Economics and Business Universitas Jambi, 2025)
This study investigates the influence of capital expenditure, economic growth, and fiscal stress on the financial performance of Regency/City Governments in Jambi Province from 2017 to 2023. The background of this research lies in the disparity of financial performance across regions and the growing fiscal pressures faced during and after the COVID-19 pandemic. Using a quantitative approach, the study employed secondary data from the Audit Reports of the Supreme Audit Agency and analyzed them through multiple regression analysis. The findings reveal that capital expenditure and fiscal stress have a positive and significant effect on regional financial performance, while economic growth does not significantly influence it. These results suggest that local governments’ financial outcomes are more sensitive to internal fiscal management than to macroeconomic changes. The study implies that increasing capital investment and effectively managing fiscal stress can enhance financial performance, and offers recommendations for policy and future research to support sustainable regional financial governance.